The earth memory compass : Diné landscapes and education in the twentieth century - King, Farina (University Press of Kansas, 2018)
In this innovative study, Farina King (Navajo) explores how historical changes in education shaped Navajo (Dine) collective identity and community by examining the interconnections between Dine students, their people, and Dine Bikeyah (Navajo lands). King investigates the ways that government schools, whether far, near, or on the reservation, affected Dine students' sense of home and relationships with their Indigenous communities during the twentieth century. King primarily relies on oral histories and cultural historical methodologies, which reveal how the home(land) and the mountains serve as focal points of Dine worldviews and how land, environment, and nature have formed an integral part of Dine knowledge and teaching - what she calls the Earth Memory Compass - that external educational systems failed to erase in the twentieth century.